Efeitos da paisagem sobre a estrutura da vegetação em remanescentes no município de Campo Grande, Mato Grosso do Sul - KARINA SANTOS PAULINELLI RAPOSO (2021)
One of the challenges of landscape ecology is to understand how species are affected by the great expansion of anthropized areas and related land use changes. The comprehension on how the floristic composition is established in urban and rural environments is essential to develop planning strategies in municipalities. This work aimed to characterize the vegetation structure of Cerrado remnants distributed in urban and rural areas of Campo Grande-MS, relating it to the type of land use in the surrounding landscape, in different spatial and temporal scales. We sampled 18 Cerrado fragments and compared species richness and functional diversity indices (richness, evenness, divergence and dispersion) between the eleven sampled remnants within the urban area and the seven rural remnants close to the city. We also evaluated whether species richness and functional dispersion (FDis) are affected by the surrounding matrix, in different spatio-temporal scales, through an interactive analysis, using satellite images from the years 1985, 2002 and 2018. Functional richness (FRic) was higher in urban than in rural areas. Similarly, there was no effect of land use on species richness, but the functional dispersion was negatively affected by the percentage of agriculture, and positively affected by the coverage of urban areas in the year 2018, with no variation detected over time. Our study points to the importance of knowing the history of cities, to provide the persistence of native species in the vegetation remnants, and the maintenance of their ecological functions in urban areas.